Os limites da teoria da felicidade (eudemonologia) em Shopenhauer - Souza, Dayane Aparecida Dias de (2020)
It is intended in this dissertation, to show how happiness lacks limits to our understanding, whereas needs meanings. In the same way, this work seeks to provide, through bibliographic and investigative methodological elements, how it is possible to think about man and the world from Schopenhauer. And in view of this, the chapters that follow will focus on a detailed analysis of the notion of Will and the issues intrinsic to it, as is the case with representation. Moreover, Immanuel Kant's theory will assist in a debate between thing-in-itself and Will, while theories diverge and approach at different times. Thus, arriving at the notion of moral and the exclusion of happiness in its domains. In fact, suffering and pain will be an expression and criterion for thinking about happiness, since, when they cease, a more pleasant existence is achieved. Therefore, the objective here is not inclined to pursue happiness, on the contrary, it is to interrupt the pain, at the same time the present does not discover itself tormented by uncertain evils.